2008
DOI: 10.1111/j.1440-1754.2008.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of 2D and colour Doppler ultrasound in localising longline position

Abstract: This technique is experience-dependent and complements rather than replaces the use of contrast radiography. However, some infants with an apparently acceptable longline position on contrast radiography have longlines located within the heart on echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…However, RT-US is a highly operator-dependent procedure, and it has been shown that the success rate in detecting the catheter's tip is directly proportional to the experience of the physicians performing this technique. 32 33 Our study is in line with the available evidence in this regard. Unfortunately, data about the optimal training and the learning curve are still lacking.…”
Section: Discussionsupporting
confidence: 91%
“…However, RT-US is a highly operator-dependent procedure, and it has been shown that the success rate in detecting the catheter's tip is directly proportional to the experience of the physicians performing this technique. 32 33 Our study is in line with the available evidence in this regard. Unfortunately, data about the optimal training and the learning curve are still lacking.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical studies on RT-US for tip location of ECCs show a direct correlation between the level of expertise of the clinician and the percentage of successful tip visualization. 45…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies on RT-US for tip location of ECCs show a direct correlation between the level of expertise of the clinician and the percentage of successful tip visualization. 45 In our experience, the minimum training requirements for ultrasound-based tip navigation and tip location of ECCs should include:…”
Section: Tip Location Protocolmentioning
confidence: 99%
“…During the first stage, the titles and abstracts of the articles were screened, and non-relevant articles were excluded (71). Of papers that were deemed relevant to the study objectives, 19 met the inclusion criteria and were included in the analysis [1,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Among these articles, 15 are prospective observational studies [1,11,22,23,[26][27][28][30][31][32][33][34][35][36][37], two retrospective papers [24,29] and two randomized controlled trials [21,25].…”
Section: Resultsmentioning
confidence: 99%